Mandela : the authorized biography - Sampson, Anthony, 1926-2004 (Harper Collins Publishers, 1999)
Nelson Mandela, who emerged from twenty-six years of political imprisonment to lead South Africa out of apartheid and into democracy, is perhaps the world's most admired leader, a man whose life has been led with exemplary courage and inspired conviction.